DETERMINING THE MUJTAHID MADHHAB: THE CONTRIBUTION OF ABDUL WAHHAB AL-MALIKI'S THOUGHTS ON ISLAMIC JURISPRUDENCE - Graiguer Abdelmounaim; A. Amir Firmansyah (Al'Adalah, 2023)
This research attempts to improve the procedures (conditions) for forming a mujtahid in Islamic Jurisprudence, who is worthy of being called a mujtahid in deciding issues, Commands, Prohibitions, and the permissibility of Allah. The point of forming a mujtahid is often discussed by fundamentalists and people who have difficulty "becoming a mujtahid" in our time, they claim that the ushuliyyun have made conditions that are impossible for Sharia scholars to achieve today, and they also claim that they do not need to what is required by the ushuliyyun. There are differences of opinion between the two disputing camps; to get out of the theoretical framework towards actual reality, it is necessary to create a model to become a judge, apart from the mujtahid absolute who lays the foundation (Terms - Conditions) in Istinbath because they have agreed to deny it. This research discusses the mujtahid madhhab explicitly because, in each madhhab, many scholars have reached the degree of mujtahid madhhab. The Maliki school is filled with that and other schools of thought. However, without denying other schools of view, this research will be specific to one of the scholars' Maliki, Qadhi Abd al-Wahhab al-Baghdady. Thus, it becomes clear where the origins of the formation of a mujtahid are. However, some conditions must be met, and those who want to reach the degree of the mujtahid, but cannot fulfill the lightest requirements to become a mujtahid, namely the quality - the nature of the mujtahid madhhab, then in fact, it is a destroyer of the basis of ijtihad in Shari'a.